The forecasting power of the mucin-microbiome interplay in livestock respiratory diseases - Núria Mach (Veterinary Quarterly)
Complex respiratory diseases are a significant challenge for the livestock industry worldwide. These diseases considerably impact animal health and welfare and cause severe economic losses. One of the first lines of pathogen defense combines the respiratory tract mucus, a highly viscous material primarily composed of mucins, and a thriving multi-kingdom microbial ecosystem. The microbiome-mucin interplay protects from unwanted substances and organisms, but its dysfunction may enable pathogenic infections and the onset of respiratory disease. Emerging evidence also shows that noncoding regulatory RNAs might modulate the structure and function of the microbiome-mucin relationship. This opinion paper unearths the current understanding of the triangular relationship between mucins, the microbiome, and noncoding RNAs in the context of respiratory infections in animals of veterinary interest. There is a need to look at these molecular underpinnings that dictate distinct health and disease outcomes to implement effective prevention, surveillance, and timely intervention strategies tailored to the different epidemiological contexts.